Study on the correlation between plasma concentration of voriconazole and clinical efficacy and safety in elderly patients - Li, Yueran; Xu, Huifang; Wang, Huifang; Zhang, Wen; Song, Yujia; Wang, Sheng (Frontiers in Pharmacology, 2026)
ObjectiveTo investigate the relationship between voriconazole plasma concentration, clinical efficacy, and adverse reactions in elderly patients.MethodsA retrospective analysis was conducted on the clinical data of 37 elderly patients with invasive fungal infections who received voriconazole therapy and underwent therapeutic drug monitoring. The associations between voriconazole plasma concentration, treatment efficacy, and safety were evaluated.ResultsAfter voriconazole treatment, the levels of liver function markers (ALT, AST, GGT, TBIL) significantly increased, while levels of albumin, WBC, neutrophils (NEUT), CRP, and PCT significantly decreased in elderly patients. Voriconazole plasma concentration was negatively correlated with albumin, calcium, and WBC, and positively correlated with ALT, AST, CRP, and PCT (P < 0.05). Multivariate analysis identified glucocorticoid use as an independent factor influencing voriconazole concentration (P < 0.05). No significant association was found between voriconazole concentration and dosage or clinical efficacy (P > 0.05), but a significant correlation was observed with the incidence of hepatotoxicity (P = 0.042), with an optimal predictive threshold of 4.5 μg/mL (AUC = 0.858).ConclusionVoriconazole plasma concentrations in elderly patients vary widely, and concentrations exceeding 4.5 μg/mL do not enhance efficacy but are associated with an increased risk of hepatotoxicity, warranting close monitoring in clinical practice.